2022
DOI: 10.1002/er.8087
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance by heteroatom‐doped reduced grapheneoxide‐TiO2‐based nanocomposites as photoanodes in dye‐sensitised solar cells

Abstract: Summary The photoanode in a dye‐sensitised solar cell (DSSC) plays a crucial role in achieving a high power conversion efficiency (PCE). It supports the sensitiser and acts as a transporter of photo‐excited electrons from the sensitiser to the external circuit. These two functions are enhanced by a large surface area and a fast charge transport rate. Typically, the photoanode consists of titanium dioxide (TiO2) nanoparticles. If the nanoparticles are deposited on a carbonaceous substrate, it facilitates the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 83 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Various approaches have been explored to incorporate 3D graphene materials into a semiconductor (typically TiO 2 ) to form composite photoanodes, including reduction of GO 98–101 and CVD 47,102–104 approaches. For example, it was demonstrated that the introduction of rGO into TiO 2 in a photoelectrode increased the PCE by 55.3%.…”
Section: Dssc Applications Of 3d Graphenementioning
confidence: 99%
“…Various approaches have been explored to incorporate 3D graphene materials into a semiconductor (typically TiO 2 ) to form composite photoanodes, including reduction of GO 98–101 and CVD 47,102–104 approaches. For example, it was demonstrated that the introduction of rGO into TiO 2 in a photoelectrode increased the PCE by 55.3%.…”
Section: Dssc Applications Of 3d Graphenementioning
confidence: 99%